Informing food system transformation with foresight: Partners adopting the use of foresight and metrics tools - Mohan, Anisha; Anisimova, Evgeniya; Wolday, Tsega (2024)
Better-informed national policy choices – Governments and other decision makers in at least five countries contribute to and use foresight analysis to better reflect climate and other risks in policy dialogues and decision-making, including policies and investments designed to make food, land, and water systems more resilient, while recognizing synergies and trade-offs with other goals relating to nutrition, livelihoods, equity, and the environment.